2023
DOI: 10.3389/fmed.2023.1181188
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of small airway dysfunction by impulse oscillometry and spirometry in chronic obstructive pulmonary disease and asthma with and without fixed airflow obstruction

Abstract: BackgroundSmall airways play a major role in the pathogenesis and prognosis of chronic obstructive pulmonary disease (COPD) and asthma. More data on small airway dysfunction (SAD) using spirometry and impulse oscillometry (IOS) in these populations are required. The objective of this study was to compare the two methods, spirometry and IOS, for SAD detection and its prevalence defined by spirometry and IOS in subjects with COPD and asthma with and without fixed airflow obstruction (FAO).DesignThis is a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In patients with chronic obstructive pulmonary disease, reactance, Fres, and AX were better than resistance parameters in stratifying degree of air trapping and were significantly correlated with RV/TLC [ 24 , 25 ]. IOS is more sensitive than spirometry in detecting SAD in asthma patients without fixed airway obstruction [ 26 ]. Additionally, IOS demonstrates greater sensitivity in detecting SAD compared to FEF25%-75% in symptomatic patients with preserved pulmonary function [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic obstructive pulmonary disease, reactance, Fres, and AX were better than resistance parameters in stratifying degree of air trapping and were significantly correlated with RV/TLC [ 24 , 25 ]. IOS is more sensitive than spirometry in detecting SAD in asthma patients without fixed airway obstruction [ 26 ]. Additionally, IOS demonstrates greater sensitivity in detecting SAD compared to FEF25%-75% in symptomatic patients with preserved pulmonary function [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no recommendation of which spirometry parameter is the best predictor of SAD [49]. The study that compared these two methods found that for normal lung function IOS may be more sensitive, while spirometry is a more sensitive method for detecting SAD in abnormal lung function [50].…”
Section: Discussionmentioning
confidence: 99%
“…In an observational study of asthmatics with normal spirometry, peripheral airways dysfunction was detected by oscillometry in 54.1% of patients while spirometry-defined peripheral airways dysfunction was detected in only 10% of patients [30 ▪ ]. Another study showed oscillometry was more sensitive than spirometry in detecting peripheral airways dysfunction in asthma patients without fixed airway obstruction, while spirometry was superior in detecting peripheral airways dysfunction in patients with fixed airway obstruction [31]. The high prevalence of peripheral airways dysfunction in asthma, especially when spirometry is normal, makes this variable an especially attractive clinical tool.…”
Section: Peripheral Airways Dysfunction Symptoms and Response To Trea...mentioning
confidence: 99%